KAJIAN YURIDIS PEMBUKTIAN PASAL 81 AYAT (2) UU RI NO.23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK (Studi Kasus Putusan Hakim Nomor17/Pid.Sus/2015/PN.Skt.). - HARTONO, EDI (Dinamika Hukum, 2016)
The purpose of this study is to assess the evidence of the facts that proved to be a violation of Article 82 of Law No.23 of 2002 on the Protection of Children in Decision Judge No. 17 / Pid.Sus / 2015 / PN.Skt and examines the legal considerations which indicate the presence of legal protection for child victims of the Award. Background this research that in the jurisdiction of the District Court Surakarta there are cases of violations of the law against Article 82 of the Child Protection Act. The case has been decided in the case No. 17 / Pid.Sus / 2015 / PN.Skt. In the decision will be reviewed the facts revealed at the hearing, especially from the point of proof as well as from the point of consideration. The research method consists of the type of normative juridical research, the necessary data is secondary data, the nature of descriptive and normative analysis done qualitatively. The results of the study concluded that the verification done by the judges begins with disclosure of the facts in the trial of the case occurred, ie criminal cases persuade intercourse. After revealing about the facts of the law is then associated with the elements of the offenses discussed in indictment. In this case, on the basis of the evidence and the evidence is there, then the accused is legally and convincingly of committing criminal offenses which the accused as first indictment that is in violation of Article 82 paragraph (1) of Act 23 of 2002 on Child Protection. Keywords : Analysis of Judicial Evidence Article 82 of Law 23 of 2002, Decision No. 17 / Pid.Sus / 2015 / PN.Skt